Application of the Canva Application Media in Learning to Produce Javanese Advertising Texts for Class XI Students at Mataram High School, Semarang - Ajjahro, Alyya Syafira Qoirunisha; Alfiah, Alfiah; Zaidah, Nuning (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This research aims to describe the results of applying the Canva application media in learning to write advertising texts for class XI students at SMA Mataram Semarang. This is motivated by the fact that there are still some students who still have difficulty expressing ideas, expressing their creativity, lack of vocabulary and students' low understanding of writing advertising texts using Javanese, so that students are less active in learning to write. In this research, a descriptive quantitative approach was used, while the design used in this research was a pre-experimental design in the form of a one-shot case study involving only one group without having to take samples. The data obtained in this research was collected through questionnaires accompanied by documentation.The results of this research are: 1) in the knowledge aspect competency test, a percentage of 87% or 14 students got a complete score above the KKM and 2 children or 13% got an incomplete score. From these results, the final average value was 86.25. 2) in the skills aspect of the competency test, a percentage of 94% or 15 students received a complete score and 6%, with 1 child getting an incomplete score. From the data processing, a final average score of 90.5 was obtained in the skills aspect. Based on the analysis of the data obtained, learning to write advertising texts using the Canva application as a medium has quite a big influence on the learning activities of writing advertising texts for class XI.2 students at Mataram High School, Semarang.